Distribution and vegetation reconstruction of the deserts of northern China during the mid‐Holocene. Issue 14 (23rd July 2014) - Li, Qin; Wu, Haibin; Guo, Zhengtang; Yu, Yanyan; Ge, Junyi; Wu, Jianyu; Zhao, Deai; Sun, Aizhi
Abstract Desertification is potentially a serious threat to society, and therefore, it is critical to understand how deserts may respond to future climate change. The mid‐Holocene (6 ± 0.5 14C ka) was warmer than present, and the distribution of deserts at this time may have implications for understanding their response to future warming. Here we reconstruct the distribution of deserts in northern China during the mid‐Holocene by combining data on vegetation type and the sedimentary facies of aeolian deposits. The results demonstrate that during the mid‐Holocene, the deserts retreated northwestward to the location of the modern 300 mm isohyet. Most of the Eastern Desert was stabilized with steppe or forest‐steppe vegetation, whereas the Western Desert exhibited no significant change and remained mobile, occupied by desert vegetation. The deserts in northern China were greatly reduced during the mid‐Holocene because of the enhancement of the East Asian summer monsoon in a warmer climate than today.